Caracterização morfoestrutural e dos parâmetros genéticos de um grupo genético de ovinos naturalizados sul-mato-grossenses - Oliveira, Daniele Portela de (2012)
Two works were carried out to make the morphostructural characterization of females and young males of naturalized Sul-mato-grossenses sheep as well as to estimate the variance components and genetics parameters. For the first work were realized 20 morphometric measurements and one weight for 338 animals belonging to Anhaguera-Uniderp and UFGD. The statistical, descriptive analyses and Pearson correlation were carried out through SAS software. For the second work was used information of 594 weights from 211 lambs belonging to Technology Center of Sheep from Anhaguera-Uniderp. The estimation of variance components for birth weight (BW), weight at 50 days (W50), weight at 90 days (W90), average daily gain from birth to 50 day (ADG0-50), average daily gain from 50 to 90 days (ADG50-90) and average daily gain from birth to 90 days (ADG) in unicaracter and bicaracter analyses were carried out through Bayesian inference. For the first work the morphometric measurements of females and young males from head and limbs region showed short variation. However, greater variation was observed in morphometric measurements taken from torso region. These indicate that torso region need be inserted in breeding programs like a selection criterion. The Pearson correlation coefficients between morphostructural characteristics from females and young males, appears to have a certain harmony degree in morphostructural model. The females are characterized by animals with relatively large head, torso with proportional features and good angulation. The gender did not influence the characteristics of head region and body weight in young animals. However, the characteristics of other regions, such as thoracic perimeter and posterior width of rump measured in the trunk, and the perimeter of carpal and metacarpal in the limbs were influenced by gender in young animals. For the second work the estimates of heritability ranged from unicaracter analyses (0.22 to 0.47) and the bicaracter analyses (0.13 to 0.78). The maternal environmental permanent effect was higher in birth weight and in the average daily gain from birth to 50 day. Estimates of heritability, maternal environmental permanent effect participation, phenotypic and genetic correlations indicate that selection for average daily gain from birth to 90 days would imply increases in weight at 50 days, weight at 90 days and average daily gain from 50 to 90 days of the lambs with no significant increase in birth weight and average daily gain from birth to 50 days.